Overview of hospitalizations by ambulatory care sensitive conditions in the municipality of Cotia, Brazil - Renata Laszlo Torres; Suely Itsuko Ciosak (SciELO, 2014)
Objective To describe the profile of Hospitalizations by Amulatory Care Sensitive Conditions (HACSC), in the Municipality of Cotia, from 2008 to 2012. Method ecological, exploratory, longitudinal study with a quantitative approach. Data on HACSC, by age group and sex, were obtained from the Department of the Unified Health System. For data analysis descriptive statistics were used. Results During the period, there were 46,676 admissions, excluding deliveries, 7,753 (16.61%) by HACSC. The main causes were cerebrovascular diseases, 16.96%, heart failure, 15.50%, hypertension, 10.80% and infection of the kidney and urinary tract, 10.51%. Regarding gender, HACSC occurred predominantly in males. There was a greater number of HACSC at extreme age ranges, especially in the elderly. Conclusion Chronic diseases predominate among the leading causes of HACSC and there was no significant difference between sex.